2008
DOI: 10.1371/journal.ppat.1000207
|View full text |Cite
|
Sign up to set email alerts
|

The Host Cell Sulfonation Pathway Contributes to Retroviral Infection at a Step Coincident with Provirus Establishment

Abstract: The early steps of retrovirus replication leading up to provirus establishment are highly dependent on cellular processes and represent a time when the virus is particularly vulnerable to antivirals and host defense mechanisms. However, the roles played by cellular factors are only partially understood. To identify cellular processes that participate in these critical steps, we employed a high volume screening of insertionally mutagenized somatic cells using a murine leukemia virus (MLV) vector. This approach … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
55
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(58 citation statements)
references
References 70 publications
(62 reference statements)
3
55
0
Order By: Relevance
“…The viral genome plasmids pMMP-nls-LacZ, pCMMP-EGFP, pCMMP-SEAP-IRES-GFP, pCMMP-IRES-GFP, pCMMP-CD4-EGFP, pHIV-TVA800-hcRED, pRET, RCASBP(A)-AP, pLEGFP, pQCLIN, and pLenti6/V5-GW/lacZ have been described previously (5). The viral genome plasmid pCMMP-luciferase was generated by replacing the enhanced green fluorescent protein (EGFP) gene in pCMMP-EGFP with the firefly luciferase gene (fLuc) from pGL3-Basic (Promega, Madison, WI).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The viral genome plasmids pMMP-nls-LacZ, pCMMP-EGFP, pCMMP-SEAP-IRES-GFP, pCMMP-IRES-GFP, pCMMP-CD4-EGFP, pHIV-TVA800-hcRED, pRET, RCASBP(A)-AP, pLEGFP, pQCLIN, and pLenti6/V5-GW/lacZ have been described previously (5). The viral genome plasmid pCMMP-luciferase was generated by replacing the enhanced green fluorescent protein (EGFP) gene in pCMMP-EGFP with the firefly luciferase gene (fLuc) from pGL3-Basic (Promega, Madison, WI).…”
Section: Methodsmentioning
confidence: 99%
“…The source and growth conditions for Chinese hamster ovary cells (CHO-K1), CHO-TVA800, human embryonic kidney 293T cells, THP-1, and human Jurkat cells were described elsewhere (5,30). Mouse NIH 3T3 and EL4 cells were obtained from the ATCC (Manassas, VA) and cultured as suggested by the distributor.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…34,36 It was recently shown that PAPSS1 influenced retroviral replication by affecting a step during provirus establishment. 37 It is noted that multiple SNPs associated with HCC clustered within the PAPSS1 ATP sulfurylase domain that included exons 6 -12 and 3 0 -untranslated region. Two rare missense variants in this domain have been reported in other races; one of which can change in vitro substrate kinetic properties.…”
Section: Discussionmentioning
confidence: 99%